Multi-biobank summary data Mendelian randomisationdoes not support a causal effect of IL-6 signalling on riskof pulmonary arterial hypertension - Woolf,B; Perry,JA; Hong,CC; Wilkins,MR; Toshner,M; Gill,D; Burgess,S; Rhodes,CJ (European Respiratory Journal, 2024)
In the most comprehensive analysis to date, this study failed to detect an association of genetically predicted CRP-weighted IL-6 signalling or CRP-weighted IL-6R signalling with PAH risk using all available PAH GWAS data https://bit.ly/3T5h5uj